THE CONTRIBUTION OF TOURISM TO THE STATE DEVELOPMENT (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
In recent years, consistent measures have been taken to develop the tourism industry in Uzbekistan, including creating as much convenience as possible, increasing the competitiveness of the industry, improving the quality of services provided, and actively promoting the national tourist product in the world market. This article provides information about the contribution of the tourism sector to the development of the state.